Aid targeting to fragile and conflict-affected states and implications for aid effectiveness - David Carment; Yiagdeesen Samy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
While significant amounts of foreign aid have been allocated to the group of so-called fragile and conflict-affected states in recent years, it is not clear whether that aid is targeted to where it is most needed. This paper extends recent work by Carment and Samy, and focuses on aid targeting in fragile states by using the Country Indicators for Foreign Policy fragility index together with sectoral aid flows from the Organisation for Economic Co-Operation and Development's Creditor Reporting System. Specifically, it considers six country-cases from a threefold typology of states and evaluates the performance of these countries in terms of their fragility relative to the types of aid that they have received. The paper argues that aid is poorly targeted in fragile states, and by considering the sectoral allocation of aid it also contributes indirectly to the related issue of aid effectiveness.
Keywords: C00; O10; O11; O19; 330; Aid effectiveness; aid targeting foreign aid; fragile states; fragile and conflict-affected states